2019
DOI: 10.1371/journal.pone.0217360
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and expression dynamics of MTP genes under various spatio-temporal stages and metal stress conditions in rice

Abstract: Metal Tolerance Proteins (MTPs) are the class of membrane proteins involved in the transport of metals, mainly Zn, Mn, Fe, Cd, Co and Ni, and confer metal tolerance in plants. In the present study, a comprehensive molecular analysis of rice MTP genes was performed to understand the evolution, distribution and expression dynamics of MTP genes. Exploration of the whole genome re-sequencing information available for three thousand rice genotypes highlighted the evolution and allelic diversity of MTP genes. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
5
19
1
Order By: Relevance
“…Under different heavy metal (Co, Cd, Ni) stress conditions, downregulation of most TaVTL genes was observed in roots and up‐regulation of most of the TaVTL genes was observed under Co stress. A similar trend in expression (downregulation in roots and upregulation in shoots) has been observed for many Metal Tolerance Protein ( MTP ) genes under different heavy metal stress conditions (Ram et al, 2019). These results highlight important role of TaVTL genes in heavy metal stress tolerance in wheat.…”
Section: Vit and Vit‐like (Vtl) Transporters In Different Plant Speciessupporting
confidence: 65%
“…Under different heavy metal (Co, Cd, Ni) stress conditions, downregulation of most TaVTL genes was observed in roots and up‐regulation of most of the TaVTL genes was observed under Co stress. A similar trend in expression (downregulation in roots and upregulation in shoots) has been observed for many Metal Tolerance Protein ( MTP ) genes under different heavy metal stress conditions (Ram et al, 2019). These results highlight important role of TaVTL genes in heavy metal stress tolerance in wheat.…”
Section: Vit and Vit‐like (Vtl) Transporters In Different Plant Speciessupporting
confidence: 65%
“…Compared with that of previous report, three new MTP genesn were found in P. trichocarpa [20]. The number of MTPs in P. trichocarpa was only second to N. tabacum among the plant species in which the MTPs have been identified [5,8,[22][23][24][25][26][27][28]. However, despite the large number of PtrMTPs, the homolog of AtMTP2 in P. trichocarpa was not detected.…”
Section: Evolution and Differentiation Of Ptrmtp Genes As Well As Thecontrasting
confidence: 62%
“…The predicted results of the subcellular localization indicated that all StMTPs are located in the vacuole which agreed with the results of Gao (2020). The predicted results of the TMHMM Server v. 2.0 analysis showed that StMTP4 has a transmembrane domain that is similar to OsMTP6 (without the domain) (Ram et al 2019). StMTP2 has 12 transmembrane domains similar to 14 in Brassica rapa var.…”
Section: The Expression Patterns Of Stmtp In Different Tissues Under supporting
confidence: 82%